Pediatric and adult Out-of-Hospital cardiac arrest incidence within and near public schools in British Columbia: Missed opportunities for Systematic AED deployment strategies. (December 2022) - Liang, Li Danny; Leung, K.H. Benjamin; Chan, Timothy C.Y.; Deakin, Jonathan; Heidet, Matthieu; Meckler, Garth; Scheuermeyer, Frank; Sanatani, Shubhayan; Christenson, Jim; Grunau, Brian
Abstract: Background: Systematic automated external defibrillator(AED) placement in schools may improve pediatric out-of-hospital cardiac arrest(OHCA) survival. To estimate their utility, we identified school-located pediatric and adult OHCAs to estimate the potential utilization of school-located AEDs. Further, we identified all OHCAs within an AED-retrievable distance of the school by walking, biking, and driving. Methods: We used prospectively collected data from the British Columbia(BC) Cardiac Arrest Registry(2013–2020), and geo-plotted all OHCAs and schools(n = 824) in BC. We identified adult and pediatric(age < 18 years) OHCAs occurring in schools, as well as nearby OHCAs for which a school-based externally-placed AED could be retrieved by a bystander prior to emergency medical system(EMS) arrival. Results: Of 16, 409 OHCAs overall in the study period, 28.6 % occurred during school hours. There were 301 pediatric OHCAs. 5(1.7 %) occurred in schools, of whom 2(40 %) survived to hospital discharge. Among both children and adults, 28(0.17 %) occurred in schools(0.0042/school/year), of whom 21(75 %) received bystander resuscitation, 4(14 %) had a bystander AED applied, and 14(50 %) survived to hospital discharge. For each AED, an average of 0.29 OHCAs/year(95 % CI 0.21–0.37), 0.93 OHCAs/year(95 % CI 0.69–1.56) and 1.69 OHCAs/year(95 % CI 1.21–2.89) would be within the potential retrieval distance of a school-located AED by pedestrian, cyclist and automobile retrieval, respectively, using the median EMS response times. Conclusion: While school-located OHCAs were uncommon, outcomes were favourable. 11.1% to 60.9% of all OHCAs occur within an AED-retrievable distance to a school, depending on retrieval method. Accessible external school-located AEDs may improve OHCA outcomes of school children and in the surrounding community.